2017
DOI: 10.1155/2017/8978527
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Risk Factors of Recurrent Mooren’s Ulcer

Abstract: Purpose To investigate the clinical characteristics of Mooren's ulcer in East China and to identify the potential risk factors that affect the recurrence of Mooren's ulcer. Methods We reviewed the medical records of 95 patients (100 eyes) diagnosed with Mooren's ulcer from May 2005 to December 2014. The patients were classified into recurrent and nonrecurrent groups and followed up for 18 months. The difference between two groups was estimated. The patients in the recurrent group were subdivided according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
0
14
0
3
Order By: Relevance
“…The average age at onset is about 50 years. 10 Mooren's ulcer is thought to be an organ-specific autoimmune disease because a cornea-associated antigen is found in patients' corneal stroma. However, the etiopathogenesis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average age at onset is about 50 years. 10 Mooren's ulcer is thought to be an organ-specific autoimmune disease because a cornea-associated antigen is found in patients' corneal stroma. However, the etiopathogenesis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…1,10 Previous research has indicated that the risk factors for Mooren's ulcer include corneal infection, trauma, and surgery. 10 The ulcerations can develop unilaterally or bilaterally with a pseudopterygium or at the donor site after pterygium surgery. 7 The coexistence of Mooren's ulcer and a pterygium is extremely rare; only two cases have been reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…Зажившие истонченные участки остаются помутневшими. Иногда зажившая роговица представлена только десцеметовой оболочкой со слоем задней стромы, покрытой эпителием [13]. Острота зрения может быть снижена за счет неправильного астигматизма, обусловленного рубцеванием периферической зоны.…”
Section: клиническая картинаunclassified
“…Mooren’s ulcer (MU) is an inflammatory chronic ulcerative keratitis that initially affects the periphery of the cornea, and later progresses circumferentially and centrally, ultimately ending in perforation. 1,2 It can be either unilateral or bilateral (50%), and the scleras are typically preserved. 2 Clinically, it presents with intense pain, photophobia, and epiphora.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It can be either unilateral or bilateral (50%), and the scleras are typically preserved. 2 Clinically, it presents with intense pain, photophobia, and epiphora. Although the etiology and pathogenesis are usually multifactorial and remain unclear, organ-specific autoimmunity seems to be the most accepted theory.…”
Section: Introductionmentioning
confidence: 99%